Design thinking development of general science teacher students that has been managed to learn according to steam education - Phoomsoong, Pawarisorn (Journal of Technical and Engineering Education, 2023)
The purpose of this research was to develop the design thinking of general science teacher students. To have a passing score of 70 percent by organizing learning activities according to the STEAM Education approach. and to study the satisfaction of general science teachers students towards learning management according to the STEAM Education approach. The target group for this research consisted of 58 people. The tools used in the research were a learning management plan according to the STEAM Education Approach design thinking test, a design thinking behavior observation form, and a satisfaction assessment form. The data were analyzed using percentage, mean, and standard deviation. which researched two operating cycles, and the research results are as follows: In Cycle 1, students had an average design thinking score of 14.7 out of 20 points, representing 73.5%, and passed the criteria for 58 out of 58 students. In Cycle 2, they improved and developed activities from Cycle 1 by organizing meaningful activities. Analyze and synthesize data to lead to a summary of the problem and practice design and planning process skills. The creation of novelty items found that students had an average design thinking score of 16.1 out of a full score of 20, representing 80.5 percent, and 58 students passed the criteria.